Relationship Between Human Leucocyte Antigen Class I and Class II and Chronic Idiopathic Urticaria Associated With Aspirin and/or NSAIDs Hypersensitivity - Maria Luisa Pacor; Gabriele Di Lorenzo; Pasquale Mansueto; Nicola Martinelli; Maria Esposito-Pellitteri; Paola Pradella; Laura Uxa; Gaetana Di Fede; GiovamBattista Rini; Roberto Corrocher (Mediators of Inflammation)
Background. HLA genes play a role in the predisposition of several diseases. The aim was to analyze the prevalence of HLA class I phenotypes and HLA-DRB1* genotype in patients with CIU associated with ASA and NSAIDs hypersensitivity (AICU). Methods. 69 patients with AICU, and 200 healthy subjects. Results. Subjects with HLA-B44 and HLA-Cw5 antigens were more represented in patients with AICU than in control group. Subjects with HLA-A11, HLA-B13, HLACw4, and HLA-Cw7 antigen were more represented in control group than in patients with AICU. Multiple logistic regression demonstrated an association of HLA-Cw4 and HLA-Cw7 with a lower risk of AICU, whereas carriers of HLA-B44 phenotype had a higher risk of AICU. No differences were found between patients and controls as regards to HLA-DRB1* genotype. Conclusions. We observed an association between some HLA class-I antigens and AICU. To the best of our knowledge this is the first description of such association.